Considerations on evaluation of health facilities management under the model of Social Organizations of Health: the case of Grajaú General Hospital - Tibério, Amanda Alves; Souza, Erica Macedo; Sarti, Flávia Mori (Saúde e Sociedade, 2010)
OBJECTIVES: Since the 1990s, in light of a scenario of limited government resources to finance essential public services to address population needs, new public administration models have been implemented. One of the main models was the delegation of public hospitals management to Organizações Sociais de Saúde (OSS - Social Organizations of Health) in the state of São Paulo. The paper proposes a structure for the evaluation of public health policy management through OSS in the city of São Paulo, starting from the case of Grajaú General Hospital. METHODS: Evaluation was centered on socio-economic and demographic variables from local population and their articulation with structural variables available from the primary healthcare network, as well as infrastructure data from the selected hospital and reports from the OSS during the period from 2004 to 2007. RESULTS: The region presents a significant deficit in primary healthcare units, which results in overload of low complexity health services demand in the hospital. Results from the comparative evaluation between public health services' supply and demand in the region, crossing information on population profile and health services provided by the OSS, indicate that the hospital adapted its structure to meet the population's essential needs. Nevertheless, it was also verified that implementing one single hospital in a high social vulnerability region is insufficient to satisfy all the population's demands; thus, it is necessary to create a network of primary healthcare units to support hospital actions in public health, especially to assume low complexity health services, so that the hospital can focus on middle and high complexity health services.